Innovation and Firm Survival In Start-Ups - Floyd, Joseph (Université d'Ottawa / University of Ottawa, 2016)
Using data from the Kauffman Firm Survey (KFS), this thesis explores the effects that innovation activities has on the survival of new firms. The KFS follows 4,928 American start-ups from 2004 to 2011. A probit model is used to examine the relationships that may exist between a number of different variables relating to innovation and survival. The results indicate that firms that invest in research and development (R&D) and machinery and equipment persistently are more likely to survive than those that do not, or those that only invest once in these types of innovative business activities. Also, with regards to intellectual property (copyrights, trademarks and patents), firms that hold these types of intellectual property have a better chance of survival than those that do not hold any intellectual property.
Keywords: start-up; innovation; R&D